Capability Of 3D Printing Technology In Producing Molar Teeth Prototype - Ahmad, Mohd Nazri; Abdul Rasib, Amir Hamzah; Tarmeze, A. A. (Praise Worthy Prize, 2020)
3D printing technology is used to build a prototype of thirty molar teeth. Additive manufacturing has referred to solid free-form manufacturing, computer automated manufacturing, and layered manufacturing. In addition, RP models can be utilized for testing in order to evaluate the precision of development of molar teeth. Meanwhile, reverse engineering technology is to scan the image data of thirty original teeth in order to form a high-resolution 3D surface data. Lately, the application of 3D printing technology in orthodontic practices has increased. However, before introducing 3D printing technology to new areas of orthodontics, its accuracy and how the technology can be used need to be evaluated. The thirty extracted molar teeth have been selected as a sample of the study. The stereolithography files of thirty teeth have been converted into physical models using two types of 3D printing technologies which are powder base (Project 460plus) and liquid based (Project HD3500). The result of this study is to measure the capability of powder and liquid based Rapid Prototyping technology by using the paired t-test. The analysis will create an alpha, which is the significant level for each parameter. Otherwise, the null hypothesis is attempted in order to find evidence against the hypothesis test. The p-value has been less than 0.05, therefore, the rejection of the null hypothesis is justified. Lastly, the aim of this paper is to verify that powder and liquid based 3D printing technologies are accurate to be used in orthodontic application